Soil resource acquisition mechanisms, nutrient concentrations and growth in perennial grasses - Saint Pierre, Carolina (2004)
Species historically heavily grazed may have been selected for grazing-resistance traits associated with improved nutrient use efficiency (Chapin and Slack, 1979). Higher root length density (RLD) and vesicular-arbuscular mycorrhizae (VAM) colonization have been associated with greater nutrient acquisition in perennial grasses, thus contributing to competitive ability (Jackson and Caldwell, 1996). This is especially true in unproductive environments where competition for belowground resources is strong (Jackson and Caldwell, 1996). Mycorrhizal fungi can affect competitive interactions among plants by improving soil nutrient uptake (Marschner and Dell, 1994; Mohammad et al., 1998). However, lack of or even negative responses have been obtained under increased levels of mycorrhizal colonization (Fitter and Hay, 1983).